Polysomnographic nighttime features of Restless Legs Syndrome: A systematic review and meta-analysis - Geng, Chaofan; Yang, Zhenzhen; Zhang, Tingting; Xu, Pengfei; Zhang, Hongju (Frontiers in Neurology, 2022)
ABSTRACT Background: Restless Legs Syndrome (RLS) can be defined as a sleep disorder. Polysomnographic (PSG) studies have been used to explore the night sleep characteristics of RLS, but their relationship with RLS is still not fully understood. Methods: We searched PubMed, EMBASE, and the Cochrane Library electronic literature databases to identify research literature comparing the differences in polysomnography between RLS patients and healthy controls (HC). Results: This review identified 26 studies for meta-analysis. Our research mainly found that total sleep time (TST) min, sleep efficiency (SE)%, N2, the rapid eye movement sleep (REM)% were significantly decreased in patients with RLS compared with HCs, while wake time after sleep onset (WASO) min, sleep latency (SL) min, stage shifts (SS), awakenings number (AWN), N1%, rapid eye movement sleep latency (REML), and arousal index (AI) were significantly increased. Additionally, there was no significant difference between N3%, slow wave sleep (SWS) %, and apnea hypopnea index (AHI) index. Conclusion: Our systematic review showed that sleep continuity and architecture are disturbed in RLS patients, which further illustrates the changes in sleep structure in patients with RLS. Additionally, further studies are needed on underlying mechanisms and associations with neurodegenerative diseases.